Technology education and presentation of knowledge using educational posters within the EU project conception - TVARÚŽKA, VÁCLAV (Journal of Education, Technology and Computer Science, 2016)
The paper deals with the part project activities for popularisation of science and technologyfocused on popularisation and technology education. The accent put on information technologyand internet sources blocked the impact of printed media. There is described the strategy of medialeffects and transferring of knowledge through educational posters focused on the project Windowsof Science Wide Open. CZ 1.07/2.3.00/45.0004. Educational posters present scientific subjects inintegrating knowledge of various subjects of science and technologies. This form of medial impacthad positive reactions among pupils and teachers of primary and secondary schools and we recommendtheir other use within projects.